Maternal Supplementation with Lacticaseibacillus rhamnosus GG Improves Glucose Tolerance and Modulates the Intestinal Microbiota of Offspring - Dayane Correia Gomes; José Enrique Meza Alvarado; Jesus Alejandro Zamora Briseño; Cynthia Cano Sarmiento; Alberto Camacho Morales; Rubi Viveros Contreras (Diseases)
Introduction: Consuming hypercaloric diets during pregnancy induces metabolic, immune, and maternal intestinal dysbiosis disorders. These conditions are transferred to the offspring through the placenta and breastfeeding, increasing susceptibility to metabolic diseases. We investigated the effect of L. rhamnosus GG supplementation on offspring maternally programmed with a hypercaloric diet. Methods: Our study involved sixteen female Wistar rats aged ten weeks, which were divided into four groups based on their diets: control (Ctrl), cafeteria (CAF), control + probiotic (PRO), and cafeteria + probiotic (CPRO). The control + probiotic and cafeteria + probiotic groups received a daily oral administration of 250 μL of L. rhamnosus GG cell suspension (equivalent to 109 UFC) for nine weeks. The body weight of the animals was recorded weekly, and their food intake was monitored every 24 h. An oral glucose tolerance test was conducted on the offspring at seven weeks of age. At the ninth week of age, animals were euthanized, and blood, tissues, and organs were collected. Results: Maternal supplementation with L. rhamnosus GG decreased food intake and the average birth weight, improved glucose sensitivity, and lowered the levels of LDL, cholesterol, triglycerides, and mesenteric adipose tissue in offspring compared with the control and cafeteria groups. Conclusions: Our findings indicate that supplementing with LGG during maternal programming could protect offspring from metabolic disruptions caused by a hypercaloric maternal diet.